2023
DOI: 10.3847/1538-4365/acb349
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-Ray to Radio Multiwavelength SED Analysis of Local U/LIRGs in the GOALS Sample with a Self-consistent AGN Model including a Polar-dust Component

Abstract: We conduct hard X-ray to radio multiwavelength spectral energy distribution (SED) decomposition for 57 local luminous and ultraluminous infrared galaxies observed with the Nuclear Spectroscopic Telescope Array and/or Swift/Burst Alert Telescope in the GOALS sample. We modify the latest SED-fitting code X-CIGALE by implementing the infrared (IR) CLUMPY model, allowing us to conduct the multiwavelength study with the X-ray torus model XCLUMPY self-consistently. Adopting the torus parameters obtained by the X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 431 publications
1
6
0
Order By: Relevance
“…a These parameters were fixed in the GALFIT fits.θ inc = 20°. A comparison between the SKIRTOR and clumpy torus models was also discussed byYamada et al (2023), and a similar conclusion was drawn by the authors. We note that we relied on the SKIRTOR model in the SED fitting, as it has been generally used in CIGALE and makes it easy to compare our results with other ones.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…a These parameters were fixed in the GALFIT fits.θ inc = 20°. A comparison between the SKIRTOR and clumpy torus models was also discussed byYamada et al (2023), and a similar conclusion was drawn by the authors. We note that we relied on the SKIRTOR model in the SED fitting, as it has been generally used in CIGALE and makes it easy to compare our results with other ones.…”
supporting
confidence: 77%
“…It is natural to consider the same torus geometry used in the SED analysis; it is the SKIRTOR torus model, which considers a two-layer structure (Stalevski et al 2016), but there was no X-ray model that was built by considering the geometry. Therefore, we decided to alternatively adopt the clumpy torus structure, whose models were available in both IR and X-ray bands (Miyaji et al 2019;Yamada et al 2023). We adopted the IR one of Nenkova et al (2008a; see also Nenkova et al 2008b) and the X-ray one of Tanimoto et al (2019).…”
Section: Simple Model Fittingmentioning
confidence: 99%
“…Among these objects, Yamada et al (2021) identified 57 U/LIRG systems that had been observed with hard X-rays, which totaled 84 individual nuclei in the optical band, and found significant hard X-ray detection from 40 AGNs from these nuclei. Yamada et al (2023) performed hard-X-ray-to-radio SED decomposition for these 57 U/LIRGs (or 72 component sources resolved in the Herschel 70 μm band). They cataloged the intrinsic AGN luminosities for the 40 hard X-ray-detected AGNs in the multiwavelength bands, containing two Herschel-unresolved dual-AGN systems and 36 resolved single AGNs.…”
Section: Goals Samplementioning
confidence: 99%
“…First, we establish useful diagnostics for identifying buried AGNs. Specifically, we employ a similar method to our previous work (Yamada et al 2019) but using, together with [O IV], 12 μm AGN luminosities (designated as L 12,AGN ; e.g., Yamada et al 2023) derived through spectral energy distribution (SED) analysis and also using [Ne V] 14.32 μm data as a supplement. The SED data are much more easily obtained than L 12,nuc .…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we consider a simple geometric model and neglect detailed radiative transfer given that the light-curve quality is insufficient to constrain the complicated physics that could be highly degenerate. Our torus model contains five parameters: the inclination angle (θ = 0°means a face-on view), inner radius R in (in units of parsecs), outer-to-inner radius ratio Y, torus half-opening angle σ, and radial power-law index p. Specifically, since we are measuring the ensemble SF in a narrow wavelength range (λ rest ∼ 1.4-2.8 μm in W1 and λ rest ∼ 2.0-3.8 μm in W2), the clouds are expected to be the hottest dust concentrated near the sublimation radius (T ∼ 1500 K, R  1 pc), as opposed to the polar dust component (T ∼ 100-200 K, R ∼ 100-1000 pc) that dominates the emissions at λ ∼ 20 μm, and contribute little to the W1 and W2 bands (e.g., Hönig et al 2013;Lyu & Rieke 2018;Yamada et al 2023). Therefore, we assume that the torus has a thin-wall geometry by fixing Y to a small value of 1.5 7 and neglect the polar component in our model.…”
Section: Idealized Light Curvesmentioning
confidence: 99%